Co‐expression of NF‐κB‐p65 and phosphorylated NF‐κB‐p105 is associated with poor prognosis in surgically resectable non‐small cell lung cancer. Issue 3 (24th January 2018) - Lin, Gen; Li, Chao; Huang, Cheng; Zhuang, Wu; Huang, Yunjian; Xu, Haipeng; Miao, Qian; Hu, Dan
Abstract: Nuclear factor‐kappa B (NF‐κB) as a prognostic marker remains unclear in non‐small cell lung cancer (NSCLC). Here, we studied NF‐κB‐p65 (p65) expression and phosphorylated NF‐κB‐p105 (p‐p105) expression in NSCLC and correlated the finding with overall survival (OS) and clinicopathological features. A total of 186 archival samples from patients with surgically resectable NSCLC were probed with p65 and p‐p105 (Ser 932). The p65‐positive expression and p‐p105‐positive expression were defined as distinct nuclear p65 and cytoplasmic p‐p105 labelling in at least 1% of tumour cells, respectively. The positive staining of p65 alone, p‐p105 alone and co‐expression of p65 and p‐p105 were observed in 61 (32.8%), 90 (48.4%) and 35 (18.8%) patients, respectively. Co‐expression of p65 and p‐p105 but not of either p65 or p‐p105 alone was associated with a poor prognosis. Patients with co‐expression of p65 and p‐p105 had a shorter OS than others, median OS 26.5 months versus 64.1 months, HR 1.85 (95% CI: 1.18–2.91), P = 0.007. There was no statistically significant association between clinicopathological characteristics and either p65 or p‐p105 alone or co‐expression of p65 and p‐p105. This indicates that co‐expression of p65 and p‐p105 was a poor prognostic factor, and pathologic studies of NF‐κB expression could include multiple pathway components in NSCLC.